Efektivitas Penyelesaian Tugas Mahasiswa Universitas Pamulang dengan Pemanfaatan ChatGPT - Rani Ade Putri; Sekarayu Embun Padmi (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
This study aims to examine the extent to which the utilization of ChatGPT can increase the effectiveness of Pamulang University students in completing academic assignments. This type of research is quantitative research with a descriptive approach. The analysis technique used was a survey through a Google Form questionnaire involving 120 respondents. Respondents of this study were Pamulang University students from all study programs and regular lectures. The results showed that in general the utilization of ChatGPT can increase the effectiveness of student academic task completion. This is indicated by the results of measuring five indicators of effectiveness which indicate that the use of ChatGPT can significantly increase the effectiveness of student task completion. ChatGPT proved to be useful as a learning tool that can facilitate students in managing time and improving the quality of academic work. Thus, the research hypothesis which states that the utilization of ChatGPT can increase the effectiveness of student task completion can be accepted. The results of this study are expected to illustrate the importance of applying AI technology in education